KONSELING INDIVIDU DENGAN TEKNIK SELF-MANAGEMENT UNTUK MENGURANGI PERILAKU AGRESIF PADA SANTRI (STUDI KASUS KLIEN “A” YANG MENJADI KORBAN BROKEN HOME) - Zahwa Juhi; Komaruddin; Zhila Jannati (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Aggressive behavior is an action taken by an individual intentionally to injure or harm another person physically or verbally. This study aims to describe the aggressive behavior of client "A", determine the factors that cause aggressive behavior of client "A", determine the application of individual counseling with self-management techniques to reduce aggressive behavior on client "A" who is a victim of a broken home. , and to find out the description of aggressive behavior in client "A" who was a victim of a broken home after applying individual counseling with self-management techniques. This type of research is field research, this research approach is qualitative with the case study method. The subjects of this study were client "A", friends of client "A" and administrators of the girls' dormitory. Data collection techniques used are observation, interviews and documentation. While the data analysis techniques used are pattern matchmaking, data explanation and time series analysis. The results showed that the description of aggressive behavior experienced by client "A" prior to individual counseling with self- management techniques was that he often ran away from responsibility to himself, students and friends, did not like to socialize, often broke promises or often lied. likes to be praised and cared for, has no awareness of teamwork, likes torturing plants and small animals and often starts fights. There are factors that influence the aggressive behavior of client "A" namely personal conditions, conflicts in the family, community and school environment. The application of individual counseling with self- management techniques is carried out in three stages, namely the initial stage of counseling, the middle stage and the final stage of counseling. The description of aggressive behavior of client "A" after applying individual counseling with self-management techniques experienced a change in behavior where client "A" felt more directed and had goals in living life, and tried to be able to reduce, control and regulate behavior in terms of emotions, speech and action.